Chasing momentum. (3rd August 2015) - Pirie, Scott; Chan, Ronald King To
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to find out why and how institutional investors in Hong Kong use momentum in the investment process. Design/methodology/approach – This study is based on interviews with 25 institutional investors based in Hong Kong, all of whom had practical investment experience of at least three years and direct responsibility for making investment decisions. Findings – Nearly all the managers interviewed use momentum strategies, and they gave three main reasons for this. First, they find momentum works in practice, particularly in the short term. Second, they believe recent changes in market conditions, such as higher volatility and widespread news coverage, have increased momentum effects. Third, they say institutional factors matter. Frequent monitoring of performance is now the norm, and this tends to focus on short-term results. Originality/value – This study complements earlier quantitative research that shows momentum strategies is a method commonly used in investment decisions. It also adds to our knowledge of what institutional investors actually do in practice, and what factors influence their application of momentum strategies.